Therapeutic effect of pulsed electromagnetic field on bone wound healing in rats. (2nd January 2021) - Liu, Yingxin; Hao, Lijuan; Jiang, Liyan; Li, Haitao
ABSTRACT: This study aimed to investigate the therapeutic effect of pulsed electromagnetic field (PEMF) on bone wound in rats as a potential therapy for bone fracture-related conditions. Male rats, aged 3 months, were used to construct model of bone wounding. Wound models were randomly selected to receive PEMF therapy at 1 to 10 mT intensity. Models that did not receive PEMF therapy were used as control. The serum concentrations of calcium (Ca), phosphorus (P) and alkaline phosphatase (ALP) were determined. Bone density and biomechanical properties of callus were measured using a tensile tester. Compared with control, rats subjected to PEMF therapy had similar weight gain, but significantly higher levels of serum Ca and ALP ( P < .05) at 5 and 10 mT, while the serum level of P remained unchanged after PEMF therapy. The bone mineral density of callus increased after the therapy, particularly, after 5 and 10 mT therapy ( P < .05). Biomechanical measurements showed that 21 days after the therapy, the maximum load, fracture load, elastic load and bending energy were significantly greater in rats receiving 5 and 10 mT PEMF therapy as compared with control ( P < .05). Our experiments demonstrate that PEMF at 5 and 10 mT can significantly accelerate wound healing and enhance the repairing ability of bone tissue.